2005
DOI: 10.1097/01.brs.0000160988.40890.1d
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Recovery of Patients With Cervical Myelopathy After Surgical Decompression

Abstract: Knee proprioception was impaired in cervical myelopathy and recovered after surgical posterior decompression. Proprioceptive improvement at 2 weeks correlates with the degree of improvement in JOA scores at 2 years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…4,9,12 However, the recovery rate is lower than that for cervical myelopathy (50-70%). [16][17][18] This disparity might be because the upper extremities are not involved in most instances of thoracic myelopathy and, as a result, activities of daily living are less impaired; 4,19 this may result in a masking of symptoms and a subsequent delay in surgical intervention (in this study, the mean duration of symptoms 22.2 months). In addition, the thoracic cord might not be able to recover as well post-decompression as the cervical cord, resulting in the difference in recovery rates.…”
Section: Discussionmentioning
confidence: 80%
“…4,9,12 However, the recovery rate is lower than that for cervical myelopathy (50-70%). [16][17][18] This disparity might be because the upper extremities are not involved in most instances of thoracic myelopathy and, as a result, activities of daily living are less impaired; 4,19 this may result in a masking of symptoms and a subsequent delay in surgical intervention (in this study, the mean duration of symptoms 22.2 months). In addition, the thoracic cord might not be able to recover as well post-decompression as the cervical cord, resulting in the difference in recovery rates.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, patients complain of body sway and difficulty in moving their extremities. It is well-known that patients with cervical myelopathy have impaired proprioception abilities [ 1 2 3 4 ]. To assess impaired upper extremity proprioception, patients with myelopathic hands can be objectively evaluated using the 10-seconds test and hand function test [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 It was also shown that proprioceptive loss recovered after surgery earlier than muscle strength. 9 The present results demonstrated that there was significant correlation between the scores of the hand function and the JOA scores, indicating there was a good association between the impairment of hand function and the extent of cervical myelopathy. Furthermore, there was significant correlation between scores of the hand function and grasp powers.…”
Section: Discussionmentioning
confidence: 59%
“…2 Recently, it is reported that knee proprioception was impaired in cervical myelopathy and recovered after surgery. 8,9 Therefore, it is hypothesized that impairment of joint proprioception or light touch sensation may also affect the hand function of myelopathy patients. We measured the degree of proprioceptive impairment of the hand as well as that of light touch sensation loss, and assessed the association between hand function and proprioceptive impairment in patients with cervical myelopathy.…”
mentioning
confidence: 99%